Case studies in disaster mitigation and prevention - Grover, Himanshu; Islam, Tanveer (Butterworth-Heinemann, 2021)
Case Studies in Disaster Mitigation and Prevention: Disaster and Emergency Management: Case Studies in Adaptation and Innovation series presents cases illustrating efforts to reduce human and material losses associated with disasters. This volume demonstrates that mitigation is an ongoing phase in which communities continually pursue long-term hazard resistance and reduction. Cases illustrate the importance of risk assessment in the development of mitigation strategies through hazard mapping and multi-hazard mitigation planning. Cases also illustrate approaches to reduction risk through structural and non-structural means, giving consideration to benefits or limitations of these strategies in different contexts. The contributions of different mitigation activities to disaster risk reduction efforts are examined using the Sendai Framework for Disaster Risk Reduction.